INOTE : aplicativo para controle e educação financeira para jovens - Oliveira, Luciano da Silva (2021)
In search of collaborating with an economic and financial scenario, as well as contributing to the financial education of young people by providing help in making more autonomous and conscious financial decisions, this work developed a mobile application (iNote) aimed at financial organization as a way of insertion of financial education in the daily lives of young people from Roraima. In the literature it is evidenced that this subject should be treated as soon as possible and for this reason, it was decided to carry out the study with students from public and private schools, regarding financial education, to carry out and identify the before and after the application of the methodology. using the application, in addition to introducing theoretical knowledge on the subject. Data collection was carried out and three questionnaires were prepared, two of which were answered by ten students aged between 12 and 18 years old and one answered by school managers. The first questionnaire contained 22 closed questions and aimed to measure the level of students' financial knowledge, the second with the aim of validating the application and measuring the effect of financial education associated with technology presented 17 closed and two open questions, and the third the 10 questions were directed to school managers in order to identify whether the topic of financial education is included in the teaching plan. As for the results, the application (iNote) provided a better quality of life for users who used it, through financial education, in which it prepared young people for the next stages of their lives, adulthood. With financial education being included in society, it gradually ceases to be a consumer-only society with a high level of indebtedness, generating in society a conscious consumption of what is necessary for their lives, in addition to the theoretical and practical contribution with students.